Prospective evaluation of follow-up in melanoma patients in Germany – Results of a multicentre and longitudinal study. Issue 5 (March 2015) - Livingstone, E.; Krajewski, C.; Eigentler, T.K.; Windemuth-Kieselbach, C.; Benson, S.; Elsenbruch, S.; Hauschild, A.; Rompel, R.; Meiss, F.; Mauerer, A.; Kähler, K.C.; Dippel, E.; et al.
Abstract Background Patient numbers requiring long-term melanoma surveillance are constantly rising. Surveillance is costly and guideline recommendations vary substantially. Methods In this German nationwide study, information on surveillance and treatment of patients diagnosed with melanoma and melanoma in situ (MMis) between April and June 2008 was prospectively collected over four years. Additionally, patient self-report questionnaires were evaluated to assess anxiety, depression, health-related quality of life, socio-demographic information and use of disease specific health information sources at year 4 after primary diagnosis. Results Complete data was available for 668 patients from 67 centres, of whom 96.0% were in regular melanoma surveillance. In year 3–4 of surveillance, only 55.6% of locoregionary metastases were detected during surveillance visits. Only 33.3% were self-detected by the patient even though 69.4% were documented as being clinically visible or palpable. Costs of 4 year surveillance of 550 patients without tumour recurrence (stage I–IIC and MMis) accumulated to 228, 155.75 €. Guideline-adherence for follow-up frequency, lymph node ultrasound, S100 serum level tests and diagnostic imaging recommendations was approximately 60% in year 3–4 of surveillance. Multivariate regression analysis showed that certain patient/tumour characteristics and regional differences were significantly associated with guideline deviations. The percentage of patients who exceeded published cut-off scores indicating clinically relevant symptoms of anxiety and depression were significantly increased. Patients frequently reported lack of psychosocial support and education but ascribed great importance to these. Conclusions We recommend further reduction of melanoma follow-up in low-risk melanoma patients and improvement of psycho-social support and patient education for all melanoma patients.